Glucarpidase Intervention for Delayed Methotrexate Clearance. (July 2014) - Cavone, Jennifer L.; Yang, Daisy; Wang, Alice
Objective: To review and evaluate the current published literature on the effectiveness and safety of glucarpidase and to determine its potential role in clinical practice.Data Sources: A PubMed literature search from 1946 to January 2014 was performed using the search terms carboxypeptidase G2, glucarpidase, high-dose methotrexate, and leucovorin rescue . Additional references were identified by reviewing the references from the PubMed search articles.Study Selection and Data Extraction: English-language clinical trials and retrospective studies assessing the safety and effectiveness of glucarpidase were included. Case reports were excluded.Data Synthesis: A total of 5 non-randomized, prospective studies and 1 retrospective study evaluated the effectiveness and safety of glucarpidase in patients receiving high-dose methotrexate. In these studies, glucarpidase conferred a >87% reduction in serum methotrexate concentrations (sMTX) and was well tolerated. Although a substantial reduction in sMTX was observed, clinically significant outcomes such as the need for dialysis, time to administration of next chemotherapy cycle, and methotrexate toxicity-related mortality were not consistently evaluated.Conclusions: Glucarpidase is effective in lowering sMTX in patients with delayed methotrexate clearance and renal dysfunction. Considering the relatively high cost of glucarpidase, it should be reserved for specific patients who have not responded to standard supportive care measures.